2021
DOI: 10.1093/g3journal/jkaa053
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate linear mixed model enhanced the power of identifying genome-wide association to poplar tree heights in a randomized complete block design

Abstract: With the advances in high-throughput sequencing technologies, it is not difficult to extract tens of thousands of single nucleotide polymorphisms (SNPs) across many individuals in a fast and cheap way, making it possible to perform genome-wide association studies (GWAS) of quantitative traits in outbred forest trees. It is very valuable to apply traditional breeding experiments in GWAS for identifying genome variants associated to ecologically and economically important traits in Populus. Here, we reported a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…Because of the unbalanced nature of the dataset, we used methods that maximize statistical power for GWA in unbalanced studies (George and Cavanagh 2015 ; Xue et al 2017 ; Chen et al 2021 ). For within-year GWA, we used the one-stage method, in which a mixed model is fit with plot-level phenotypes as the response and environmental (e.g., trial, year, location), genotypic (e.g., line, family), genetic background (e.g., relationship/kinship matrices, population structure components), and SNP information as fixed or random effects (Xue et al 2017 ; Chen et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the unbalanced nature of the dataset, we used methods that maximize statistical power for GWA in unbalanced studies (George and Cavanagh 2015 ; Xue et al 2017 ; Chen et al 2021 ). For within-year GWA, we used the one-stage method, in which a mixed model is fit with plot-level phenotypes as the response and environmental (e.g., trial, year, location), genotypic (e.g., line, family), genetic background (e.g., relationship/kinship matrices, population structure components), and SNP information as fixed or random effects (Xue et al 2017 ; Chen et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the unbalanced nature of the dataset, we used methods that maximize statistical power for GWA in unbalanced studies (George and Cavanagh 2015 ; Xue et al 2017 ; Chen et al 2021 ). For within-year GWA, we used the one-stage method, in which a mixed model is fit with plot-level phenotypes as the response and environmental (e.g., trial, year, location), genotypic (e.g., line, family), genetic background (e.g., relationship/kinship matrices, population structure components), and SNP information as fixed or random effects (Xue et al 2017 ; Chen et al 2021 ). Plant breeding experiments can include large numbers of individuals and/or trials, making one-stage GWA computationally intensive when complex variance–covariance structures (e.g., relationship/kinship matrices) are included to control for background genetic effects (George and Cavanagh 2015 ; Xue et al 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, the new assembly provides a specific parental reference sequence for extracting tens of thousands of SNP genotypes across an F 1 hybrid population in which the P. deltoides I-69 was as a female parent ( Mousavi et al 2016 ; Tong et al 2016 ). With the large number of SNPs, high-density genetic linkage maps of the parents can be constructed and thus the QTL mapping or genome-wide association studies could be conducted for growth and woody traits ( Tong et al 2020 ; Chen et al 2021 ). Second, this genome sequence allowed us to identify genes unique to the cultivar I-69 through orthologous analysis ( Supplementary Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput genotyping technology and phenotyping platforms have enabled large-scale marker-trait association analysis, such as GWAS, to precisely dissect the genetic architecture of plant traits [222]. In trees, several studies have reported many putative genomic regions associated with variation of related-traits to tree phenology [223,224], wood properties [118,120,165,[225][226][227][228][229], growth (i.e., wood volume, tree height and diameter; [108,111,117,120,226,[230][231][232], resistance to pests and diseases [233][234][235][236], among others. For example, McKown et al (2018) [223] implemented a GWAS analysis with the motivation to understand the molecular mechanisms of the variation in bud-break of flowers in Populus trichocarpa Torr.…”
Section: Genome-wide Association Studies (Gwas)mentioning
confidence: 99%